Circular saw-related fatalities: A rare case report, review of the literature, and forensic implications - Janík, Martin; Straka, Ľubomír; Novomeský, František; Krajčovič, Jozef; Hejna, Petr (Legal medicine (Tokyo, Japan), 2016)
Fatalities attributed to powered circular saws appear to be vanishingly rare events with highly wounding and rapidly incapacitating effects. When they do occur, they are mainly self-inflicted in nature. We report the suicide committed by a 79-year-old man using a self-made circular table saw. Autopsy confirmed that the man received multiple heterogeneously distributed saw-type impacts to the head and neck resulting in complete amputation of the upper skull and partial beheading. Homemade or modified commercial sawing instruments and the resultant injuries pose a number of forensic challenges starting from the death scene investigation, continuing with technical examinations, and concluding with determining the manner of death. As with all deaths due to sharp force injuries, fatalities involving power tools such as chainsaws, circular, and band saws warrant a high degree of suspicion of criminal activity and require diligence during all phases of the death investigation.
Keywords: Suicide; Morphology; pitva; Neck Injuries; poranění obličeje; penetrující rány; lidé; Wounds, Penetrating; Amputation; Forensic Pathology; Circular saw; sebevražda; Decapitation; traumatická amputace; poranění krku; Male; Aged; Facial Injuries; senioři; mužské pohlaví; Autopsy; soudní patologie; Amputation, Traumatic; Humans